Antecedents and consequences of using social media for personal finance among Indonesian Gen Z - Nia Noer Wahidah; Ihsan Hadiansah (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
As a digital tool, social media plays an increasingly important role in people’s everyday life. One of the generations that depend heavily on this tool is Generation Z, often abbreviated as Gen Z. In Indonesia only, social media reached 277,7 million users with 42% users at the age of 24 or below. Among the purposes of social media usage, personal finance rose as a topic that has been gaining more attention of Gen Z, as the importance of financial management appeal to this digital native generation. Previous research in China, later on, provoked the interest of the researchers to investigate the antecedents and consequences of social media usage for personal finance among Indonesian Gen Z. Findings of this research reveals the that social media perceived usefulness, social media compatibility, and perceived risk has a positive and significant relationship with the use of social media for personal finance, while perceived ease of use did not show any significant result. Current use of social media for personal finance and personal finance outcomes also proven to encourage the future use of social media for personal finance. Thus, this study recommends individual or organizations in the field of personal finance (financial consultants, financial planning, etc.) to leverage the use of social media, considering its advantages for the consumers. This study adopted the model and variables from a previous study by Cao et al., (2020) however, to the knowledge of the researcher, this study is the first study to examine the model on Indonesian Gen Z.